Climate Investments as a Condition for Overcoming the Warming in the World and in Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2017)
To overcome the warming of the planet is important to use such a new tool of climate finance as climate investments and its innovative component - «green bonds». The problem is the uncertainty of the content of the following economic categories: climate finance, investment climate, climate innovations that makes them difficult to use. This article is devoted to solve this problem. Climate investments are means of the international climate funds (primarily Green Climate Fund, EU funds and other international organizations), the budget means of individual states and their regions and particular communities and means of particular businesses and citizens that are used to maintain and improve the climate on the planet. In recent years «green bonds», which are used primarily by the international financial institutions, have emerged as innovative form of climate finance. «Green Bonds» are bonds, funds from the placement of which are primarily directed at developing renewable energy sources. «Green Bonds» are located not by only international financial institutions, banks and private companies, but also governments, municipal and local authorities. Overall, the government of Ukraine needs to develop the system of incentives to attract foreign and domestic investments, especially in the development of renewable energy sources (RES) associated with the use of wind, water, solar, biomass and more. This is prevented by the following issues: the unstable political and economic situation in the country, leading to a rise in the cost of renewable energy projects in Ukraine.